Method for producing colloidal silica
Patent Information
- Application Number
- JP2025135746
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-08-18
- Publication Date
- 2026-10-14
AI Technical Summary
【0013】 本発明によれば、表面が変性されたコロイダルシリカを得るにあたり、変性処理の変性率を向上させることができる。
Smart Images

Figure 2026167375000001 
Figure 2026167375000002
Abstract
Description
[Technical Field]
[0001] This invention relates to a method for producing colloidal silica. [Background technology]
[0002] Several methods have been proposed and implemented for the industrial production of high-purity colloidal silica, including ion exchange of an aqueous sodium silicate solution, thermal decomposition of silicon tetrachloride, and hydrolysis of organosilicate in a water-alcohol mixed solvent in the presence of an acid or alkali catalyst. However, the hydrolysis of organosilicate is particularly suitable for producing high-purity colloidal silica with low metal impurity content because it allows the use of highly pure organosilicate, catalyst, and solvent in the reaction, resulting in very few impurities derived from these raw materials. Several methods for hydrolyzing organosilicate have been proposed to date.
[0003] Here, regarding colloidal silica used in various applications, particularly in the field of semiconductor wafer polishing, with the increasing integration of LSIs today, various types of metal wiring and oxide films exist on a single wafer, and each semiconductor wafer requires polishing performance suited to its specific needs. Therefore, colloidal silica with subtly different compositions and properties is required.
[0004] Furthermore, for applications where even slight alkali metal impurities are undesirable, such as binders for hard coatings and ceramics, chromic acid-based metal surface treatment agents, and ground improvement injection agents, acidic colloidal silica is required, and several methods for producing such acidic colloidal silica are known.
[0005] For example, the applicant of this application has investigated a method for easily producing colloidal silica having predetermined properties, such as spherical colloidal silica, which does not require special post-treatment such as acid treatment, ion exchange treatment, or modification treatment, has an extremely low content of metal impurities, including alkali metals, and whose average particle size, as determined by particle size distribution analysis using an electron microscope, is in the range of 5 to 500 nm, with a standard deviation of 20 or less and a polydispersity index of 0.15 or less. As a result, the applicant has proposed that neutral colloidal silica with a pH of 5 to 8 can be easily produced without special post-treatment such as acid treatment or ion exchange treatment by using an easily hydrolyzable organosilicate with a fast hydrolysis rate and using a specific hydrolysis catalyst as the hydrolysis catalyst, and by adding this hydrolysis catalyst so that the ratio of hydrolysis catalyst (A) to silica (B) in the reaction mixture at least at the end of the reaction {catalyst remaining molar ratio (A / B)} is below a predetermined value and carrying out the reaction (Patent Document 1).
[0006] Incidentally, in the field of polishing agents for semiconductor wafers and substrates, for example, there is a need to meet various demands in recent years. However, with conventional colloidal silica of several tens of nanometers (nm), fine adjustment during polishing is difficult, resulting in problems such as the inability to form a clean surface, residue remaining on the surface of the object being polished, and the instability of the particles themselves under acidic conditions as their zeta potential approaches the isoelectric point. Therefore, it has become necessary to adjust the electrical affinity of silica particles with the surface of the object being polished, or to modify the particles to have excellent dispersibility even under acidic conditions.
[0007] One way to address such issues is to modify the surface of colloidal silica. For example, Patent Document 2 relates to modified colloidal silica that can improve the stability of the polishing rate over time when used as an abrasive with a small amount of fine particles. According to Patent Document 2, in order to make the number distribution ratio of fine particles below a predetermined value, before applying the modification treatment, an organic solvent removal step is performed to remove the organic solvent coexisting with the colloidal silica so that the organic solvent concentration in the colloidal silica raw material produced by hydrolysis-condensation reaction (sol-gel method) is less than 1% by mass. However, after diligent investigation by the inventors, it was discovered that, surprisingly, including a step to remove the organic solvent before the modification treatment actually reduces the modification rate in the modification treatment described later.
[0008] Furthermore, for example, Patent Document 3 provides colloidal silica and a method for producing the same, which have a small average secondary particle diameter and can maintain the dispersion stability of silica particles over a long period of time even under strongly acidic conditions of pH 3 or lower. According to Patent Document 3, the above objective can be achieved by using colloidal silica that has an average secondary particle diameter of 20 nm or less as measured by dynamic light scattering, a zeta potential of -20 mV or less as measured under pH 3 conditions, and is surface-modified with sulfonic acid groups. However, after diligent research by the present inventors, it was found that the modification rate of the surface modification (the modification rate of this application, described later) is not necessarily high in the method described in Patent Document 3. [Prior art documents] [Patent Documents]
[0009] [Patent Document 1] Japanese Patent Publication No. 2007-153732 [Patent Document 2] International Publication No. 2016 / 117560 [Patent Document 3] International Publication No. 2025 / 018234 [Overview of the project] [Problems that the invention aims to solve]
[0010] Therefore, the inventors of the present invention diligently studied how to improve the modification rate of colloidal silica with a modified surface. As a result, they found that this could be achieved by devising the raw material preparation process and concentration adjustment process, as well as by applying the modification treatment to the colloidal silica at a predetermined timing, and thus completed the present invention.
[0011] Therefore, an object of the present invention is to provide a method for producing colloidal silica that can improve the modification rate of the modification treatment. [Means for solving the problem]
[0012] In other words, the gist of this invention is as follows: (1) A method for producing colloidal silica whose surface is anionically modified, A raw material preparation step involves supplying and reacting readily hydrolyzable organosilicate with a reaction solution containing a hydrolysis catalyst made of an organic amine to prepare the raw material colloidal silica, A concentration adjustment step is performed to set the solid content concentration of the raw material colloidal silica to 13% by mass or less, and the concentration of alcohols generated from the raw material preparation step to 1 to 25% by mass, A modification treatment step for modifying the concentration-adjusted raw material colloidal silica, The process includes a concentration step of concentrating the modified colloidal silica so that the residual organic solvent in the modified colloidal silica is 1% by mass or less. A method for producing colloidal silica, characterized in that the modification rate of the modification treatment in the modification treatment step is 90% or more. (2) The method for producing colloidal silica according to (1), characterized in that the modification rate in the modification treatment step is 95% or more. (3) The method for producing colloidal silica according to (1) or (2), characterized in that the pH during the modification treatment in the modification treatment step is 8.0 or less. (4) The method for producing colloidal silica according to (1) or (2), characterized in that in the raw material preparation step, the reaction is carried out under the conditions that the supply rate of the easily hydrolyzable organosilicate is less than 1.5 mass% / min relative to the total input amount of the easily hydrolyzable organosilicate, the reaction time is within 6 hours, and the reaction temperature is 80°C or lower. (5) The method for producing colloidal silica according to claim (1) or (2), characterized in that in the concentration step, the colloidal silica after the modification treatment step is concentrated so that the solid content concentration therein is 15 mass% or more. (6) The method for producing colloidal silica according to claim (1) or (2), characterized in that in the raw material preparation step, raw material colloidal silica having a cumulant average diameter measured by a dynamic light scattering method of more than 20 nm is prepared. (7) The method for producing colloidal silica according to (1) or (2), characterized in that the modification treatment step comprises a step of reacting a modifying agent having a functional group convertible to an anionic group with the colloidal silica after the concentration adjustment step, and a step of converting the functional group in the modifying agent after the reaction into an anionic group. (8) The method for producing colloidal silica according to (7), characterized in that the modifying agent has a mercapto group and / or a sulfide group, and the mercapto group and / or the sulfide group is converted into a sulfo group by treatment with an oxidizing agent to obtain colloidal silica having a sulfo group on the surface. [Advantageous Effects of the Invention]
[0013] According to the present invention, in obtaining surface-modified colloidal silica, the modification rate of the modification treatment can be improved. [Modes for Carrying Out the Invention]
[0014] <Method for Producing Colloidal Silica> The method for producing colloidal silica of the present invention essentially comprises the following steps. (a) A raw material preparation step of supplying an easily hydrolyzable organosilicate to a reaction liquid containing a hydrolysis catalyst composed of an organic amine and allowing them to react, to prepare raw material colloidal silica. (b) A concentration adjustment step of adjusting the solid content concentration of the raw material colloidal silica to 13 mass% or less, and adjusting the concentration of alcohols generated from the raw material preparation step to 1 to 25 mass%. (c) A modification treatment step of subjecting the raw material colloidal silica whose concentration has been adjusted in the step (b) to modification treatment. (d) A concentration step of concentrating the modified colloidal silica obtained in the step (c) such that the residual organic solvent therein is 1 mass% or less. Here, the modification rate of the modification treatment in the (c) modification treatment step is 90% or more. These steps are described below.
[0015] [Step (a)] First, in step (a), an easily hydrolyzable organosilicate is supplied to and reacted with a reaction solution containing a hydrolysis catalyst composed of an organic amine, to prepare colloidal silica as a raw material. In the present invention, the colloidal silica prepared in step (a) is referred to as raw material colloidal silica.
[0016] Although the particle size of the raw material colloidal silica obtained in this step (a) is not limited, from the viewpoints of avoiding the occurrence of aggregation, and the stable production of the raw material colloidal silica through the supply and reaction of the easily hydrolyzable organosilicate, the BET diameter, which is the particle size converted from the BET specific surface area, is usually preferably 5 nm or more and 80 nm or less. A more preferable lower limit is 6 nm or more, a still more preferable lower limit is 10 nm or more, and an even more preferable lower limit is 14 nm or more. On the other hand, a more preferable upper limit is 70 nm or less, a still more preferable upper limit is 60 nm or less, and an even more preferable upper limit is 50 nm or less. In this invention, the significance of preferentially defining the BET diameter is that, as will be explained later, the product may be not only monodisperse spherical but also colloidal silica manufactured by the two-dimensional or three-dimensional bonding of multiple particles. Furthermore, considering the manufacturing method of the present invention, the colloidal silica may have surface irregularities and a relatively high specific surface area. Therefore, adopting a BET diameter that is considered spherical while also considering the specific surface area is preferable for determining the performance relative to the particle shape.
[0017] Here, in this invention, the BET diameter is defined as the BET specific surface area S (unit: m²) of colloidal silica measured by the BET method. 2 ( / g) and true density ρ (unit: g / cm³) 3 This is the particle size calculated from ). Specifically, it can be determined from the following equation (1). BET diameter (nm)=6000 / (S×ρ) ···(1) Here, ρ is the typical true density of SiO2, which is 2.2 g / cm³. 3 That is the case.
[0018] Furthermore, regarding particle size, from the same viewpoint as above, and because in the case of relatively small particle sizes, there is a possibility that some parts may be difficult to grasp with an electron microscope, it is preferable that the cumulant average diameter (hereinafter sometimes simply referred to as "cumulant average diameter" or "DLS diameter") measured by dynamic light scattering, which has a wide measurement range, be 6 nm or larger, more preferably 10 nm or larger, even more preferably 15 nm or larger, and even more preferably exceeding 20 nm. On the other hand, there is no upper limit to the cumulant average diameter, but it is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less.
[0019] While commercially available colloidal silica can be used as the raw material, hydrolysis is preferred because it allows for fewer metal impurities, the production of colloidal silica with a relatively large surface area, and the manufacture of highly uniform particles. The hydrolysis method involves supplying a silica source to a reaction solution containing a hydrolysis catalyst and initiating the hydrolysis reaction. Alternatively, a method is used in which an easily hydrolyzable organosilicate is supplied as the silica source to a reaction solution containing a hydrolysis catalyst made of an organic amine, and initiating the hydrolysis reaction, because it allows for easy control of particle size.
[0020] Here, the silica source preferably used in step (a) is an easily hydrolyzable organosilicate with a fast hydrolysis rate. Preferably, an easily hydrolyzable organosilicate is one in which 10 g of organosilicate and 100 g of pure water with impurities of 0.1 ppb or less are subjected to a hydrolysis reaction at 25°C under stirring, and the hydrolysis reaction is completed within 1 hour. Specifically, examples of such easily hydrolyzable organosilicates include trimethyl silicate (hydrolysis reaction time until hydrolysis reaction is completed: about 3 minutes), tetramethyl silicate (hydrolysis reaction time: about 5 minutes), triethyl silicate (hydrolysis reaction time: about 5 minutes), and methyltrimethyl silicate (hydrolysis reaction time: about 7 minutes). Tetraethyl silicate and organosilicates with more carbon atoms tend to have a slow hydrolysis rate and are prone to gelation (hydrolysis reaction time: 24 hours or more in both cases), so the above-mentioned easily hydrolyzable organosilicates are preferably used.
[0021] Furthermore, the organic amines used as hydrolysis catalysts in step (a) are not limited, but one selected from quaternary ammonium compounds, tertiary amines, secondary amines, and primary amines, as well as their carbonates, bicarbonates, and silicates, or mixtures of two or more thereof, can be widely used. For example, quaternary ammonium compounds include tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), trimethylethylammonium hydroxide, trimethylethanolammonium hydroxide (choline), triethylethanolammonium hydroxide, tetrapropylammonium hydroxide, and butylammonium hydroxide, as well as their carbonates, bicarbonates, and silicates. Since a relatively high pH is desirable for the hydrolysis reaction, tetramethylammonium hydroxide (TMAH), choline, or tetraethylammonium hydroxide (TEAH) are preferred.
[0022] Furthermore, the organic amines used as hydrolysis catalysts are not limited to primary, secondary, or tertiary amines, but examples include amino alcohols, morpholines, piperazines, aliphatic amines, and aliphatic etheramines. Here, various amino alcohols can be used, including ethanolamine derivatives, but ethanolamine derivatives are preferred, such as monoethanolamine, diethanolamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, N,N-di-n-butylethanolamine, N-(β-aminoethyl)ethanolamine, N-methylethanolamine, N-methyldiethanolamine, N-ethylethanolamine, Nn-butylethanolamine, Nn-butyldiethanolamine, N-tert-butylethanolamine, and N-tert-butyldiethanolamine.
[0023] Furthermore, various morpholine derivatives can be used as morpholines among the organic amines used as hydrolysis catalysts, but morpholine, N-methylmorpholine, N-ethylmorpholine, etc. are preferred. Furthermore, various piperazine derivatives can be used as piperazines among the organic amines used as hydrolysis catalysts, but piperazine, hydroxyethylpiperazine, etc. are preferred. In addition, as aliphatic amines and aliphatic etheramines among the organic amines used as hydrolysis catalysts, suitable aliphatic amines include alkylamines having 1 to 8 carbon atoms such as triethylamine, dipropylamine, pentylamine, hexylamine, heptylamine, and octylamine. Suitable aliphatic etheramines include aliphatic etheramines having 1 to 8 carbon atoms such as 2-methoxyethylamine, 3-methoxypropylamine, 3-ethoxypropylamine, 3-propoxypropylamine, 3-isopropoxypropylamine, and 3-butoxypropylamine.
[0024] Among such hydrolysis catalysts, for example, in terms of maintaining a preferred pH range during the modification treatment in step (c) described later, it is preferable to use triethanolamine, monoethanolamine, diethanolamine, n-butylamine, n-nonylamine, dodecylamine, benzylamine, diethylamine, piperazine, pyridine, piperidine, 3-diethylaminopropylamine, dibenzylamine, and 3-ethoxypropylamine as the hydrolysis catalyst. It is more preferable to use triethanolamine, monoethanolamine, diethanolamine, benzylamine, piperazine, pyridine, 3-diethylaminopropylamine, dibenzylamine, and 3-ethoxypropylamine, and even more preferable to use triethanolamine, diethanolamine, piperazine, and dibenzylamine. Using such a hydrolysis catalyst is a preferred embodiment not only for the reasons in step (c) described later, but also in step (a), as it can suppress the occurrence of self-aggregation due to excessively rapid hydrolysis.
[0025] These organic amines used as hydrolysis catalysts can be used individually or, if necessary, as a mixture of two or more.
[0026] As mentioned above, the reaction solution must contain an easily hydrolyzable organosilicate as a silica source and a hydrolysis catalyst, but other components such as water, alcohols, aldehydes, ketones, and surfactants can be used. Preferably, the silica source, hydrolysis catalyst, and water together make up 90% by mass or more. More preferably, these make up 95% by mass or more.
[0027] In the reaction mixture of the silica source and the hydrolysis catalyst described above (hereinafter sometimes referred to as the "reaction mixture"), or in the reaction mixture after which the solid content concentration or alcohol concentration is adjusted, or the dispersion stabilization treatment with acid is performed, for example as described later (hereinafter sometimes referred to as the "reaction concentrate"), it is preferable to add the hydrolysis catalyst to the reaction system and carry out the hydrolysis reaction so that the ratio of the hydrolysis catalyst (A) to the silica (B) {catalyst residual molar ratio (A / B)} is 0.012 or less, more preferably in the range of 0.00035 to 0.012, and even more preferably in the range of 0.0035 to 0.011. This is preferable because it allows for the optimization of the pH of the reaction mixture or reaction concentrate, and also suppresses thickening and gelation.
[0028] There are no particular limitations on the method for achieving such a catalyst remaining molar ratio. Examples include continuously or intermittently introducing a silica source into a reaction vessel containing water and hydrolysis catalyst (A) such that the final catalyst remaining molar ratio (A / B) falls within the aforementioned range; continuously or intermittently introducing a hydrolysis catalyst and silica source into a reaction vessel containing only water such that the final catalyst remaining molar ratio falls within the aforementioned range; or continuously or intermittently introducing a hydrolysis catalyst and silica source into a reaction vessel containing water and a small amount of hydrolysis catalyst (A) such that the final catalyst remaining molar ratio falls within the aforementioned range.
[0029] Furthermore, it is preferable to introduce colloidal silica seeds with particle growth properties into the reaction system of the hydrolysis reaction prior to the hydrolysis reaction of the silica source, and then gradually add the silica source and hydrolysis catalyst to this reaction system so that the catalyst residual molar ratio (A / B) is within the above range. This allows for the production of colloidal silica particles of uniformity.
[0030] Furthermore, the silica source, hydrolysis catalyst, and water used as raw materials for the hydrolysis reaction preferably have a metal impurity content of 1 ppm or less, and more preferably 0.01 ppm or less, indicating high purity. This ensures that the aforementioned range of metal impurity content is satisfied for both the resulting raw material colloidal silica and the modified colloidal silica after modification.
[0031] In step (a), there are no limitations on the method for setting the BET diameter of the raw material colloidal silica and the average cumulant diameter within the above range, but it is preferable to adjust the rate at which the silica source is added to the reaction solution (supply rate), the reaction temperature, and the reaction time.
[0032] When using readily hydrolyzable organosilicate as a silica source, the supply rate is preferably less than 1.5% by mass / min of the total amount of readily hydrolyzable organosilicate added, more preferably 1.3% by mass / min or less, and even more preferably 1.2% by mass / min or less. If the supply rate is 1.5% by mass / min or more, the particles tend not to disperse evenly and do not become nearly spherical. The reason why the total amount added is used as a criterion is that the amount added varies depending on the manufacturing scale, etc., and it is preferable to consider completing the supply within the reaction time described later. In other words, it is preferable to make the supply rate as slow as possible, as this makes it easier to form the desired small particle size. There is no lower limit to the supply rate, but if the supply rate is too slow, the target particle size may not be achieved, so it is preferably 1.0% by mass / min or more of the total amount added.
[0033] Furthermore, the reaction temperature is preferably 80°C or lower, more preferably 75°C or lower, and even more preferably 70°C or lower. If the reaction temperature exceeds 80°C, the volatilization of the reaction solution increases, making it easier for the liquid composition to change, which may make it difficult to control the particle size. On the other hand, the lower limit of the reaction temperature can be set as appropriate, but if the temperature is too low, the hydrolysis reaction tends to slow down, which may promote particle growth, so it is preferable to set it to 20°C or higher.
[0034] Furthermore, the reaction time is preferably within 6 hours, more preferably within 3 hours, and even more preferably within 2 hours. If the reaction time exceeds 6 hours, the target particle size may not be achieved. On the other hand, the lower limit of the reaction time can be set as appropriate, but if the reaction time is too short, the hydrolysis reaction may not be completed, and particle formation or growth may not occur sufficiently, so it is preferably 20 minutes or more.
[0035] In step (a), it is preferable that the solid content concentration during the reaction be 3 to 13% by mass. If the solid content concentration is less than 3% by mass, particle formation and particle growth may not occur sufficiently. On the other hand, if the solid content concentration is too high, particle aggregation is likely to occur. In step (a), it is preferable that the solid content concentration of the colloidal silica after the reaction be within the range of 3 to 13% by mass.
[0036] [Step (b)] In step (b), the solid content concentration of the raw colloidal silica obtained in step (a) is adjusted to 13% by mass or less. By adjusting the solid content concentration to 13% by mass or less, even when the BET diameter and the average cumulant diameter are relatively small, the occurrence of aggregation can be reduced, and the next step (c) (modification treatment step) can be carried out without causing aggregation gelation. In other words, by keeping the solid content concentration within this range, the next step (c) (modification treatment step) can be carried out at a concentration that exhibits relatively high dispersibility. Furthermore, this makes it easier to achieve a high modification rate in the modification treatment in step (c). Preferably, the solid content concentration should be 12% by mass or less, more preferably 10% by mass or less. Here, although it is difficult to define or distinguish clearly, "aggregation gelation" generally refers to a state in which the aggregation of colloidal silica progresses further and becomes a jelly-like mass visible to the naked eye.
[0037] Here, if the solid content concentration of the raw colloidal silica obtained in step (a) is already 13% by mass or less, it is not necessary to actively adjust the solid content concentration in step (b). In that case, the process may be treated as a step to confirm the solid content concentration or a step to maintain the solid content concentration as is. Ensuring that the solid content concentration is indeed 13% by mass or less in step (b) before the modification treatment in the next step (c) is a characteristic step in obtaining a colloidal silica of the present invention that is not substantially aggregated and has a high modification rate, while still having a relatively high solid content concentration.
[0038] The method for adjusting the solid content concentration in step (b) is not limited, but it is preferable to do so by adding the same solvent as that contained in the raw material colloidal silica. The solvent to be added is preferably water and / or alcohols, more preferably water, methanol and / or ethanol, and even more preferably water and / or methanol. The solvent to be added may include, as mentioned above, water, alcohols, aldehydes, ketones, surfactants, etc.
[0039] Furthermore, in step (b), the concentration of alcohols generated from step (a) is adjusted to 1 to 25% by mass. In step (a), alcohols are generated by the hydrolysis reaction depending on the easily hydrolyzable organosilicate used as the silica source. For example, if the easily hydrolyzable organosilicate used has a methoxy group, such as trimethyl silicate or tetramethyl silicate, methanol is produced as the alcohol. If the easily hydrolyzable organosilicate used has an ethoxy group, such as triethyl silicate, ethanol is produced as the alcohol. The same applies to other types.
[0040] Here, although the detailed mechanism is not clear, it is necessary to adjust the concentration of alcohols produced from the hydrolysis reaction in step (a) to 1-25% by mass in step (b). However, it is presumed that by maintaining or adjusting the concentration of these alcohols within this range, the reaction rate of hydrolysis of modifying agents such as silane coupling agents used in the next step (c) (modification treatment step) and the subsequent condensation can be mitigated, and unintended self-condensation reactions between modifying agents such as silane coupling agents can be suppressed, thereby increasing the modification rate of the modification treatment in step (c). Furthermore, although the detailed mechanism is not clear, it is presumed that by maintaining or adjusting the concentration of these alcohols within this range, even when the BET diameter and the average cumulant diameter are relatively small due to the polarity of the solvent, the occurrence of aggregation can be reduced, and the next step (c) can be carried out without causing aggregation and gelation. The concentration of the alcohols produced can be adjusted as appropriate by the amount of easily hydrolyzable organosilicate used in step (a) or by replacing the alcohols with pure water by distillation, but it is preferable that the lower limit be 5% by mass or more, and the lower limit be 12% by mass or more. On the other hand, it is preferable that the upper limit be 20% by mass or less.
[0041] Furthermore, similar to the adjustment of the solid content concentration (13% by mass or less) in step (b) above, if the alcohol concentration of the raw colloidal silica obtained in step (a) is already 1 to 25% by mass, it is not necessary to actively adjust the alcohol concentration. In that case, the step may be to confirm the alcohol concentration or to maintain the alcohol concentration produced in step (a) as is. Ensuring that the alcohol concentration in step (b) is indeed 1 to 25% by mass before the modification treatment in the next step (c) is a characteristic step, similar to the adjustment of the solid content concentration (13% by mass or less) above, in obtaining a colloidal silica of the present invention that is not substantially aggregated and has a high modification rate, while also having a relatively high solid content concentration. These alcohols may become part of the solvent in the modification treatment in the next step (c).
[0042] The method for adjusting the concentration of the alcohols in step (b) is not limited, but when adjusting to increase the concentration of the alcohols, it is preferable to add a substance whose main component is the same organic solvent as the generated alcohols (for example, 95% by mass or more). The organic solvent added here may include water, alcohols, aldehydes, ketones, surfactants, etc., as described above. On the other hand, the method for adjusting to decrease the concentration of the alcohols is not limited, but for example, one method is to distill them from a condenser-equipped distillation tube while volatilizing them by heating. In this case, pure water may be added further.
[0043] [Process (c)] In step (c), the colloidal silica raw material, whose solid content concentration and the concentration of the alcohols produced in step (b) have been adjusted, is subjected to a modification treatment. In the present invention, anionic modification treatment is performed. Although the reason why anionic modification is preferred as the modification treatment is not entirely clear, it is presumed that anionic modification changes the surface potential of the colloidal silica, which is expected to attract the object to be polished, thereby improving the selectivity of the object to be polished. In particular, compared to colloidal silica that has not undergone modification treatment, the dispersion stability tends to improve not only in alkaline conditions but also in acidic conditions, where it is metastable and relatively prone to aggregation.
[0044] For information on anion modification treatment, see, for example, Japanese Patent Publication No. 2010-269985 and Japanese Patent Publication No. 2013-041992.
[0045] Here, the specific method of anionic modification is not limited, but a preferred method of anionic modification is, for example, a method of chemically bonding a modifying agent having an anionic group to the surface of colloidal silica. Another method is to chemically bond a modifying agent having a functional group that can be converted to anionic groups to the surface of colloidal silica by a chemical method, and then perform a treatment to convert the functional group to anionic groups. For reasons such as the efficiency of the modification treatment, the ability to introduce anionic groups into colloidal silica with good stability, and the difficulty in directly obtaining a modifying agent having anionic groups, a method using a modifying agent having a functional group that can be converted to anionic groups is preferred.
[0046] The compound (modifier) having a functional group that can be converted to an anionic group is not limited, but a silane coupling agent having a functional group that can be converted to an anionic group is a suitable example. Here, the anionic group is not limited, but examples include a sulfo group, a carboxyl group, a phosphate group, etc. It may also be a group that has ionically bonded with a cation to form a salt. Even such an anionic group will function as an anionic group in aqueous solution after the cation is removed. Examples of cations that ionically bond with the anionic group include alkali metal ions such as sodium ions and potassium ions, and alkaline earth metal ions such as calcium ions. From the viewpoint of improving the selectivity of the object to be polished, among the anionic groups, a sulfo group and a carboxyl group are preferred, and a sulfo group is more preferred.
[0047] As an anionic group, a sulfo group will be used as an example in a preferred embodiment. Examples of modifying agents having a functional group that can be converted to a sulfo group include silane coupling agents having a sulfonic acid ester group that can be converted to a sulfo group by hydrolysis, and silane coupling agents having a mercapto group and / or a sulfide group that can be converted to a sulfo group by oxidation. Of these, the method using a silane coupling agent having a mercapto group and / or a sulfide group is more preferred because it is easier to modify colloidal silica with it. In this invention, only one modifying agent may be used, or two or more may be used in combination.
[0048] Examples of silane coupling agents having a mercapto group include 3-mercaptopropyltrimethoxysilane, 2-mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, and 2-mercaptoethyltriethoxysilane. An example of a silane coupling agent having a sulfide group is bis(3-triethoxysilylpropyl)disulfide.
[0049] Among the anionic modifications, the sulfo group, which was exemplified as a preferred embodiment, will be explained as an example.
[0050] (Regarding an example of anionic modification treatment using a sulfo group) The sulfo group can be formed on the surface of colloidal silica by known methods as described above. Preferably, a modifying agent having a functional group that can be converted to a sulfo group can be chemically bonded to the surface of colloidal silica by a chemical method, and then a process is performed to convert the functional group to a sulfo group. A modifying agent having a functional group that can be converted to a sulfo group by oxidation is preferred. Among these preferred modifying agents, as described above, are silane coupling agents having a mercapto group and / or a sulfide group, which will be described as follows.
[0051] In this method, it is preferable to include a step (c1) in which the raw colloidal silica, whose solid content and the concentration of the generated alcohols have been adjusted through steps (a) and (b) as described above, is reacted in the presence of the silane coupling agent, and a step (c2) in which the reactant from step c1 is oxidized to convert the mercapto group and / or sulfide group into sulfo group. Steps c1 and c2 can also be carried out by referring to the aforementioned Japanese Patent Publication No. 2010-269985 and Japanese Patent Publication No. 2013-041992. In addition, other steps may be included as appropriate, as long as they do not impair the purpose of the present invention. Examples of other steps include adjusting the viscosity of the reaction solution and adjusting the pH.
[0052] (Step c1) In step c1, the colloidal silica raw material, whose solid content and the concentration of the generated alcohols have been adjusted through steps (a) and (b), is reacted in the presence of a silane coupling agent having mercapto groups and / or sulfide groups. This chemically bonds the silane coupling agent to the surface of the colloidal silica raw material.
[0053] The reaction in step c1 can be carried out within the appropriate temperature range for the denaturing agent, and is not limited to that range. For example, it can be carried out at a temperature of 40°C or higher and below the boiling point of the reaction solution (solvent). Preferably, to improve reactivity, the temperature is preferably 50°C or higher, more preferably 60°C or higher, and preferably below the boiling point of the reaction solution (solvent) at 100°C or lower. The reaction time is also not limited, but for example, it is preferably 10 minutes to 10 hours, and more preferably 1 to 8 hours.
[0054] In the reaction of step c1, a solvent can be added to improve the solubility of the denaturing agent and silane coupling agent, to the extent that it does not impair the objective of the present invention. Examples of such solvents include hydrophilic solvents, such as alcohols including methanol, ethanol, and isopropanol, but are not limited to these. It is more preferable to use the same alcohols as those produced by the hydrolysis reaction to obtain the colloidal silica raw material.
[0055] As previously mentioned, the amount of the above-mentioned modifying agent (silane coupling agent) used is preferably 0.1 to 10 parts by mass, more preferably 0.2 to 6 parts by mass, and even more preferably 0.3 to 4 parts by mass, per 100 parts by mass of solid content in the raw colloidal silica. That is, the amount of the modifying agent in the solid content of the modified colloidal silica is preferably 0.1 to 10% by mass, more preferably 0.2 to 6% by mass, and even more preferably 0.3 to 4% by mass. With an amount within this range, the particle surface of the colloidal silica can be sufficiently anionized. Furthermore, with such an amount, colloidal silica that has been anion-modified without aggregation and with a high modification rate and stably can be produced. Note that a solvent (water, hydrophilic organic solvent, etc.) may be used to dissolve the modifying agent during the modification treatment.
[0056] Furthermore, when performing the modification treatment, it is preferable that the pH during the modification treatment be weakly alkaline or lower, more preferably 8.0 or lower, even more preferably 7.8 or lower, and even more preferably 7.5 or lower. In other words, it is a preferred embodiment that the pH of the raw material colloidal silica after the concentration adjustment step in step (b), which is to be used in step (c), is within the above range. By setting the pH during the modification treatment within this range, the decomposition of modification agents such as silane coupling agents used can be suppressed. There is no preferred lower limit for the pH during the modification treatment, but it is preferable that the pH be 6.5 or higher, more preferably 6.8 or higher, and even more preferably 7.0 or higher.
[0057] The method for adjusting the pH during the modification treatment to the preferred range described above is not limited. For example, by appropriately selecting the hydrolysis catalyst used in step (a) described above, the raw material colloidal silica in step (a) and the raw material colloidal silica after concentration adjustment in the subsequent step (b) can be adjusted to the preferred pH range described above. As described above, by appropriately selecting the hydrolysis catalyst, it is possible to suppress excessively rapid hydrolysis and the occurrence of self-aggregation in step (a), and at the same time, the pH during the modification treatment in step c1 can also be adjusted. Therefore, selecting the preferred hydrolysis catalyst described above in step (a) is a more preferred embodiment. In addition, in step c1, the pH during the modification treatment can be adjusted by adding a known pH adjusting agent or by contacting it with a cation exchange resin (see, for example, Japanese Patent Application Publication No. 2022-152370).
[0058] The reaction in step c1 can also be understood by analyzing the functional groups introduced into colloidal silica, for example, by pulsed NMR (TD-NMR), ion chromatography, etc. 29 Qualitative and / or quantitative analysis of functional groups can be performed using methods such as Si-NMR, organic elemental analysis, and FT-IR (infrared spectroscopy).
[0059] (Step c2) In step c2, the functional groups introduced to the surface of the colloidal silica raw material in step c1 are converted to anionic groups by a chemical method. Here, we describe a method in which the functional groups introduced by a silane coupling agent having mercapto groups and / or sulfide groups are converted to sulfo groups by oxidation.
[0060] The method for converting mercapto groups and / or sulfide groups to sulfo groups by oxidation is not limited, but one method is to use an oxidizing agent. Examples of oxidizing agents include nitric acid, hydrogen peroxide, oxygen, ozone, organic peracids (percarboxylic acids), bromine, hypochlorite, potassium permanganate, and chromic acid. Among these, hydrogen peroxide and organic peracids (peracetic acid, perbenzoic acid) are preferred in terms of handling and reactivity (yield of oxidation). Furthermore, since hydrogen peroxide produces fewer by-products in the reaction, it is most preferable to use it. The amount of oxidizing agent added may be in excess of the modifying agent (silane coupling agent), but it is preferable to minimize the amount of residual oxidizing agent, and it is more preferable to use 3 to 5 moles of oxidizing agent per mole of silane coupling agent in order to ensure a sufficient oxidation reaction. The oxidation reaction is not limited, but can be carried out under suitable reaction conditions for the oxidizing agent used, as long as it does not impair the purpose of the present invention. For example, it is preferable to carry out the reaction at a temperature above room temperature but below the boiling point of the solvent used in the reaction mixture (e.g., below 100°C) for a period of 3 to 5 hours.
[0061] This step c2 allows for the production of colloidal silica having anionic groups (sulfo groups) on its surface. Step c2 may include other steps after the oxidation treatment. For example, it may include steps to remove the oxidizing agent or to adjust the pH of the solution after the reaction, and these steps can be appropriately selected and carried out without prejudice to the purpose of the present invention.
[0062] Regarding the modification treatment in step (c), a characteristic feature of the method of the present invention is its high modification rate. In particular, a high modification rate can be achieved by going through step (b) and adjusting the pH during the modification treatment in step (c) to a preferred range. The modification rate in the present invention is 90% or higher. Preferably it is 95% or higher, more preferably 98% or higher, even more preferably 99% or higher, even more preferably close to 100%, and most preferably 100%. Here, the modification rate in the present invention can be determined from the amount of modifying agent used for the modification treatment and the amount of modifying agent (converted anionic group) introduced onto the surface of the modified colloidal silica, as can be seen in the examples described later. For example, as shown in the examples, using ion chromatography analysis, the amount of functional groups of the modifying agent that are not introduced to the colloidal silica surface as unreacted (unmodified) and the amount of converted anionic groups in the modified colloidal silica solution can be quantified. By subtracting this from the amount of modifying agent added for the modification treatment, the amount introduced (modified) to the colloidal silica surface (amount of substance; amount modified by anionic groups) can be determined and expressed as a ratio to the amount of modifying agent added. 29 The rate of denaturation can also be measured using one or more analytical methods such as Si-NMR, organic elemental analysis, or FT-IR.
[0063] [Step (d)] After performing step (c), step (d) is performed to concentrate the residual organic solvent in the colloidal silica obtained after step (c) to 1% by mass or less. Preferably, the residual organic solvent is 0.1% by mass or less, more preferably 0.05% by mass or less. Reducing the residual organic solvent to this range is preferable because it allows the solid content concentration to be adjusted or increased to a predetermined range, and in the case of a highly volatile residual organic solvent, it prevents fluctuations in the concentration of colloidal silica due to the volatilization of the organic solvent. Furthermore, when using the colloidal silica of the present invention, there are advantages such as not needing to consider the resistance of residual organic solvents in the materials used at the application site.
[0064] The method for removing and concentrating the residual organic solvent is not particularly limited, and known methods can be used. For example, one method is to distill off the residual organic solvent by heating using an apparatus equipped with a distillation tube with a condenser.
[0065] In step (d), the solid content concentration can be adjusted to the desired level by concentrating the process of removing residual organic solvents and water, taking into account its intended use and purpose. In the present invention, colloidal silica that has undergone modification treatment through steps (a) to (c) described above is obtained, and even if the solid content concentration is relatively high in step (d), colloidal silica that does not aggregate substantially can be obtained. The modified colloidal silica obtained by the above modification treatment usually has a solid content concentration of about 6% by mass due to the manufacturing process, etc. However, considering the reasons for improving polishing performance and reducing transportation costs, as well as the intended use and purpose of the colloidal silica, it is preferable to make the solid content concentration in the colloidal silica after modification treatment step (c) 15% by mass or more through step (d), more preferably 17% by mass or more, and even more preferably 19% by mass or more. The upper limit of the solid content concentration is the same as described above, preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0066] The colloidal silica of the present invention can be produced by performing steps (a) to (d) described above. However, other steps may be included after step (d) as appropriate, as long as they do not impair the objectives of the present invention. For example, it is preferable to disperse and stabilize the colloidal silica after step (d). Known dispersal stabilization treatments can be used.
[0067] Colloidal silica treated with the dispersion stabilization method of the present invention exhibits excellent dispersion stability for several weeks or even several years, and does not undergo bilayer separation.
[0068] In the present invention, colloidal silica with anionically modified surfaces can be obtained with a high modification rate as described above. However, as in conventional methods, a method in which the obtained colloidal silica is used as seed particles, and a silica source is supplied to and reacted with a reaction solution containing these seed particles and the hydrolysis catalyst to grow the particle size is not excluded.
[0069] <Modified colloidal silica> The anion-modified colloidal silica produced through the aforementioned steps (a) to (d) (hereinafter referred to as "modified colloidal silica") preferably has a solid content concentration of 15% by mass or more, more preferably 17% by mass or more, and even more preferably 19% by mass or more. There is no upper limit to the solid content concentration, but it is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less.
[0070] Furthermore, as described above, the modified colloidal silica obtained by the method of the present invention has a modification rate of 90% or more. The modification rate is preferably 95% or more, more preferably 98% or more, even more preferably 99% or more, even more preferably close to 100%, and most preferably 100%. The modification rate can be measured and defined by the method described above.
[0071] Furthermore, the particle size of the modified colloidal silica, as the BET particle size, is preferably 5 nm to 80 nm, similar to the raw material colloidal silica mentioned above. A more preferable lower limit is 6 nm or more, an even more preferable lower limit is 10 nm or more, and an even more preferable lower limit is 14 nm or more. On the other hand, a more preferable upper limit is 70 nm or less, an even more preferable upper limit is 60 nm or less, and an even more preferable upper limit is 50 nm or less.
[0072] Furthermore, the particle size of the modified colloidal silica is preferably 6 nm or larger as the DLS diameter, more preferably 10 nm or larger, even more preferably 15 nm or larger, and even more preferably exceeding 20 nm. On the other hand, there is no upper limit to the cumulant average diameter, but it is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 100 nm or less.
[0073] Furthermore, modified colloidal silica is substantially free from aggregation. The reason for using the term "substantially" is as follows: Generally, methods to confirm that colloidal silica is agglomerating include electron microscopy, measuring viscosity increase, and measuring the average cumulant diameter using dynamic light scattering (DLS). However, it is difficult to fully ascertain whether each and every particle is monodisperse. Since the aforementioned methods can only grasp or understand the dispersion state of the particles with a certain degree of certainty, if there is substantially no aggregation to a degree that does not pose a practical problem, then there will be no problems in terms of the function of colloidal silica or its applications.
[0074] Furthermore, in order to more specifically understand the aforementioned "substantially non-aggregated" state, it is possible to measure it using the method described above, however, there may be some parts that are difficult to grasp with an electron microscope. For this reason, it is preferable to use dynamic light scattering (DLS) and make a judgment based on the change in the average cumulant diameter measured by it. More specifically, it is common to confirm the change (or lack thereof) in the average cumulant diameter by DLS measurement over time. For example, in the manufacturing method of the present invention, in step (d) (concentration step), the presence or absence of aggregation can be confirmed by checking the DLS measurement results before and after concentration. In other words, by understanding the presence or absence of aggregation with increasing solid content concentration, it becomes possible to confirm whether the colloidal silica has characteristics that make it prone to aggregation. This is because aggregation occurs less when the solid content concentration is relatively low, and aggregation becomes more likely as the solid content concentration increases. This tendency is usually more pronounced when the solid content concentration is 10% by mass or more, more specifically 12% by mass or more.
[0075] Among the DLS measurement methods, a more practically preferable method for determining aggregation is to measure the change in particle size by DLS measurement after holding the material under heated conditions for a certain period of time. This method allows for confirmation of whether the colloidal silica has properties that make it prone to aggregation without actively changing the solid content concentration. Specifically, as demonstrated in the examples described later, the change in the average cumulant diameter is confirmed after holding the material at a temperature of at least 60°C for 7 days, which is a temperature at which particles are prone to aggregation. If the rate of change is within 20%, it can be determined that there is no aggregation. The reason why the method of holding the material at 60°C for 7 days is preferred is that it has been found that the conditions of 60°C for 7 days are roughly equivalent to a time-dependent test of holding the material at room temperature for one year, and thus it is possible to confirm the presence or absence of aggregation in a time-dependent test of at least one year at room temperature. Preferably, the rate of change in the average cumulant diameter by DLS measurement is within 10%, more preferably within 8%, and even more preferably within 5%. Here, when performing such DLS measurements, for the reasons mentioned above, it is preferable to hold or measure the sample at a solid content concentration of 12% by mass or more, more specifically 18% by mass or more, even more specifically 19% by mass or more, preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less. The solid content concentration at this time is not limited, and it is preferable to perform the DLS measurement at a solid content concentration that is appropriate for the application and actual use.
[0076] Further, the modified colloidal silica may have any arbitrary shape and other properties depending on the application, purpose, and the like. In particular, the colloidal silica obtained by the method of the present invention preferably has a relatively high particle surface area, desirably has a large number of irregular small protrusions and an overall shape resembling a piece of konpeito sugar. Regarding such a shape, despite a large SEM average particle diameter, which is the arithmetic mean value measured from particle images observed by SEM, the BET specific surface area is large, and the particle density (true specific gravity) measured by the liquid phase displacement method is high, in other words, the particles have the property of high hardness, exhibit an excellent polishing rate, and are suitable for use as a CMP polishing agent. Therefore, the BET specific surface area is 50 m 2 / g or more, more preferably 100 m 2 / g or more. Although the upper limit of the BET specific surface area is not limited, from the viewpoint of stability and the like, it is preferably 500 m 2 / g or less, more preferably 400 m 2 / g or less.
[0077] The particle shape of the modified colloidal silica can be controlled to be monodisperse spherical (spherical product) or a shape in which particles are cohered and associated (associated product) depending on the charged composition and the like. For example, by using a relatively large amount of catalyst and introducing the organosilicate as the silica raw material into the reaction field relatively slowly, the organosilicate hydrolyzes rapidly and uniformly and grows mildly, so that the seed particles gradually grow while maintaining a spherical shape to obtain a spherical product. Further, for example, by using a relatively small amount of catalyst and introducing the organosilicate as the silica raw material into the reaction field relatively rapidly, the organosilicate hydrolyzes non-uniformly and behaves like an adhesive between particles, and as a result, an associated product in which particles are aggregated can also be obtained.
[0078] Further, the modified colloidal silica preferably has a viscosity of 1 to 100 mPa·s, more preferably 1 to 50 mPa·s, and even more preferably 1 to 20 mPa·s.
[0079] Furthermore, as mentioned above, the modified colloidal silica may be monodisperse spherical particles, or it may be aggregate particles (such as cocoon-shaped, chain-like, or branched) that appear to be formed by the two-dimensional or three-dimensional aggregation of multiple particles when observed under an electron microscope.
[0080] Furthermore, the modified colloidal silica may be adjusted to a pH that does not impair its dispersion stability, depending on the modification treatment described above. For example, in the case of the anionically modified colloidal silica, the pH is preferably 1 to 5, and more preferably 1.5 to 4.5. Adjusting the pH to this range is advantageous in terms of the dispersion stability of the colloidal silica.
[0081] Furthermore, the modified colloidal silica preferably has a metal impurity content of 1 ppm or less, more preferably 0.01 ppm or less, and even more preferably 0.0001 ppm or less. Such high-purity colloidal silica can be achieved, for example, by using a silica source, hydrolysis catalyst, and water that satisfy the above-mentioned metal impurity content as raw materials for the hydrolysis reaction when obtaining the colloidal silica raw material in the manufacturing method described later. [Examples]
[0082] Preferred embodiments of the present invention will be specifically described below based on examples and comparative examples.
[0083] [Example 1] In a 5L glass container equipped with a stirrer, thermometer, distillation tube with condenser, and organosilicate inlet tube, 3184g of pure water with a metal impurity content of 0.1 ppb or less and 3.41g of triethanolamine with a metal impurity content of 10 ppb or less were charged. While maintaining the liquid temperature in the reaction vessel at 70°C using a mantle heater, 1413g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.) with a metal impurity content of 10 ppb or less was continuously supplied over 6 hours under stirring. The resulting 625g of colloidal silica with a silica concentration of 12.6% by mass, 2767g of pure water with a metal impurity content of 0.1 ppb or less, and 7.91g of triethanolamine with a metal impurity content of 10 ppb or less were charged. While maintaining the liquid temperature in the reaction vessel at 80°C using a mantle heater, 1200g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.) with a metal impurity content of 10 ppb or less was continuously supplied over 6 hours under stirring. Various analyses were performed on the obtained colloidal silica raw material, and the results are shown in Table 1. <1> As shown.
[0084] Next, 3900g of the resulting reaction product (colloidal silica, solid content concentration 12.5% by mass, methanol concentration 14% by mass) was added to a 5L glass container, and no changes were made to the solid content concentration or methanol concentration. Then, while maintaining the temperature at 80°C, 15.6g of 3-mercaptopropyltrimethoxysilane mixed with 140.4g of methanol was continuously supplied over 6 hours. After the supply, 27.0g of 30% by mass hydrogen peroxide solution was further supplied continuously over 4 hours while maintaining the temperature at 80°C to modify the raw material colloidal silica.
[0085] After supplying hydrogen peroxide solution, the temperature in the reaction vessel was temporarily lowered to 40°C, the system was depressurized using a vacuum pump, and then heating was resumed. The reaction mixture in the reaction vessel was further heated to 52-68°C, and the generated methanol was distilled off from a condenser-equipped distillation tube at a distillation temperature of 32-67°C. Further, 250g of pure water was added while distilling off the water and methanol to obtain colloidal silica with a solid content of approximately 20% by mass. The residual organic solvent in the obtained colloidal silica was 0.1% by mass. Various analyses were performed on the obtained colloidal silica, and the results are shown in Table 1. <2> The results are shown in Table 1. The denaturation rate (anionic group modification reaction rate) was calculated using the formula described later, with the amount of modification being the amount obtained by subtracting the amount of sulfate ions quantified by anion chromatography from the amount of 3-mercaptopropyltrimethoxysilane added to the colloidal silica. Furthermore, the obtained colloidal silica was stored at 60°C for 7 days, and various analyses were performed on the obtained colloidal silica. In particular, the DLS measurement results confirmed that virtually no aggregation had occurred. The results are shown in Table 1. <3> As shown.
[0086] [Example 2] In a 5L glass container equipped with a stirrer, thermometer, distillation tube with condenser, and organosilicate inlet tube, 3184g of pure water with a metal impurity content of 0.1 ppb or less and 3.41g of triethanolamine with a metal impurity content of 10 ppb or less were charged. While maintaining the liquid temperature in the reaction vessel at 70°C using a mantle heater, 1413g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.) with a metal impurity content of 10 ppb or less was continuously supplied over 6 hours under stirring. Various analyses were performed on the obtained raw material colloidal silica, and the results are shown in Table 1. <4> As shown.
[0087] Next, 3900g of the obtained reaction product (colloidal silica, solid content concentration 12.5% by mass, methanol concentration 15% by mass) was added to a 5L glass container, and no changes were made to the solid content concentration or methanol concentration. Then, while maintaining the temperature at 80°C, 13.1g of 3-mercaptopropyltrimethoxysilane mixed with 117.8g of methanol was continuously supplied over 6 hours. After the supply, 22.7g of 30% by mass hydrogen peroxide solution was further supplied continuously over 4 hours while maintaining the temperature at 80°C to modify the raw material colloidal silica.
[0088] After supplying hydrogen peroxide solution, the temperature in the reaction vessel was temporarily lowered to 40°C, the system was depressurized using a vacuum pump, and then heating was resumed. The reaction mixture in the reaction vessel was further heated to 52-68°C, and the generated methanol was distilled off from a condenser-equipped distillation tube at a distillation temperature of 32-67°C. Further, 250g of pure water was added while distilling off the water and methanol to obtain colloidal silica with a solid content of approximately 20% by mass. The residual organic solvent in the obtained colloidal silica was 0.1% by mass. Various analyses were performed on the obtained colloidal silica, and the results are shown in Table 1. <5> The results are shown in Table 1. The denaturation rate (anionic group modification reaction rate) was calculated using the formula described later, with the amount of modification being the amount obtained by subtracting the amount of sulfate ions quantified by anion chromatography from the amount of 3-mercaptopropyltrimethoxysilane added to the colloidal silica. Furthermore, the obtained colloidal silica was stored at 60°C for 7 days, and various analyses were performed on the obtained colloidal silica. In particular, the DLS measurement results confirmed that virtually no aggregation had occurred. The results are shown in Table 1. <6> As shown.
[0089] [Example 3] In a 5L glass container equipped with a stirrer, thermometer, condenser-equipped distillation tube, and organosilicate introduction tube, 3890g of pure water with a metal impurity content of 0.1 ppb or less and 3.42g of triethanolamine with a metal impurity content of 10 ppb or less were charged. While maintaining the liquid temperature in the reaction vessel at 60°C using a mantle heater, 707g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.) with a metal impurity content of 10 ppb or less was continuously supplied over 90 minutes under stirring. Various analyses were performed on the obtained raw material colloidal silica, and the results are shown in Table 1. <7> As shown.
[0090] Next, 3900g of the resulting reaction product (colloidal silica, solid content concentration 6.4% by mass, methanol concentration 14% by mass) was added to a 5L glass container, and no changes were made to the solid content concentration or methanol concentration. Then, while maintaining the temperature at 80°C, 13.1g of 3-mercaptopropyltrimethoxysilane mixed with 117.8g of methanol was continuously supplied over 6 hours. After the supply, 22.7g of 30% by mass hydrogen peroxide solution was further supplied continuously over 4 hours while maintaining the temperature at 80°C to modify the raw material colloidal silica.
[0091] After supplying hydrogen peroxide solution, the temperature in the reaction vessel was temporarily lowered to 40°C, the system was depressurized using a vacuum pump, and then heating was resumed. The reaction mixture in the reaction vessel was further heated to 52-68°C, and the generated methanol was distilled off from a condenser-equipped distillation tube at a distillation temperature of 32-67°C. Further, 250g of pure water was added while distilling off the water and methanol to obtain colloidal silica with a solid content of approximately 20% by mass. The residual organic solvent in the obtained colloidal silica was 0.1% by mass. Various analyses were performed on the obtained colloidal silica, and the results are shown in Table 1. <8> The results are shown in Table 1. The denaturation rate (anionic group modification reaction rate) was calculated using the formula described later, with the amount of modification being the amount obtained by subtracting the amount of sulfate ions quantified by anion chromatography from the amount of 3-mercaptopropyltrimethoxysilane added to the colloidal silica. Furthermore, the obtained colloidal silica was stored at 60°C for 7 days, and various analyses were performed on the obtained colloidal silica. In particular, the DLS measurement results confirmed that virtually no aggregation had occurred. The results are shown in Table 1. <9> As shown.
[0092] [Comparative Example 1] In a 5L glass container equipped with a stirrer, thermometer, distillation tube with condenser, and organosilicate inlet tube, 510g of pure water with a metal impurity content of 0.1 ppb or less, 3412g of methanol, and 140g of 29% aqueous ammonia were charged. While maintaining the liquid temperature in the reaction vessel at 20°C using a constant temperature water bath, 425g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.), mixed with 113g of methanol and containing a metal impurity content of 10 ppb or less, was continuously supplied over 25 minutes under stirring. After that, thermal concentrated water replacement was performed under conditions of pH 7 or higher. Various analyses were performed on the obtained raw material colloidal silica, and the results are shown in Table 2. <10> As shown.
[0093] Next, 1000g of the reaction product (colloidal silica, solid content concentration 19.5% by mass, methanol concentration less than 1% by mass) was placed in a 5L glass container, and 1.7g of 29% by mass aqueous ammonia was added to reduce the viscosity. Then, 2.5g of 3-mercaptopropyltrimethoxysilane mixed with 22.5g of methanol was added dropwise over 5 minutes, and the mixture was heated. After boiling, water substitution was performed for 6 hours. After the reaction solution was cooled to 25°C, 4.3g of 30% by mass aqueous hydrogen peroxide was added, and the mixture was brought to a boil again. After boiling, water substitution was performed for 4 hours, and then the mixture was cooled to room temperature to modify the raw material colloidal silica. Various analyses were performed on the obtained colloidal silica, and the results are shown in Table 2. <11> The results are shown in Table 2. The denaturation rate (anionic group modification reaction rate) was calculated using the formula described below, with the amount of modification being the amount obtained by subtracting the amount of sulfate ions quantified by anion chromatography from the amount of 3-mercaptopropyltrimethoxysilane added to the colloidal silica. Furthermore, the obtained colloidal silica was stored at 60°C for 7 days, and various analyses were performed on the obtained colloidal silica. In particular, the DLS measurement results confirmed that virtually no aggregation had occurred. The results are shown in Table 2. <12> As shown.
[0094] [Comparative Example 2] In a 10L glass container equipped with a stirrer, thermometer, distillation tube with condenser, and organosilicate inlet tube, 8836g of pure water with a metal impurity content of 0.1 ppb or less and 13.968g of 3-ethoxypropylamine were charged. While maintaining the liquid temperature in the reaction vessel at 85°C using a mantle heater, 1534g of tetramethyl silicate (manufactured by Tama Chemical Industry Co., Ltd.) with a metal impurity content of 10 ppb or less was continuously supplied over 15 minutes under stirring. Various analyses were performed on the obtained raw material colloidal silica, and the results are shown in Table 2. <13> As shown.
[0095] Next, 900 g of the resulting reaction product (colloidal silica, solid content concentration 6.4% by mass, methanol concentration 15% by mass) was added to a 2 L glass container, and no changes were made to the solid content concentration or methanol concentration. Then, while maintaining the temperature at 80°C, 2.530 g of 3-mercaptopropyltrimethoxysilane and 11.684 g of 30% by mass hydrogen peroxide solution were added to modify the raw material colloidal silica.
[0096] Next, methanol was replaced with water while adding pure water to obtain colloidal silica with a solid content of approximately 6% by mass. The residual organic solvent in the obtained colloidal silica was 0.1% by mass.
[0097] Various analyses were performed on the obtained colloidal silica, and the results are shown in Table 2. <14> The results are shown in Table 2. The denaturation rate (anionic group modification reaction rate) was calculated using the formula described below, with the amount of modification being the amount obtained by subtracting the amount of sulfate ions quantified by anion chromatography from the amount of 3-mercaptopropyltrimethoxysilane added to the colloidal silica. Furthermore, the obtained colloidal silica was stored at 60°C for 7 days, and various analyses were performed on the obtained colloidal silica. In particular, the DLS measurement results confirmed that virtually no aggregation had occurred. The results are shown in Table 2. <15> As shown.
[0098] [Table 1]
[0099] [Table 2]
[0100] The physical properties of the obtained colloidal silica were evaluated using the following method. (1) BET specific surface area, BET equivalent particle size: Measured using NOVA4200e (Anton Paar). BET specific surface area S(m²) measured by nitrogen adsorption method (BET method) 2 The true density of SiO2 is 2.2 g / cm³ (1 / g). 3 From equation (1) above, the particle diameter derived by the equation 2727 / S is defined as the BET diameter. (2) Cumulant mean diameter (DLS diameter) by dynamic scattering method: Measured using the SZ-100 instrument (manufactured by Horiba, Ltd.). During measurement, the silica content in the sample was adjusted to 1.13 g using pure water and ammonium nitrate, and the adjusted solution was measured. (3) Silica solid content concentration: Using the SMS-70 instrument (manufactured by A&D Company, Limited), the silica concentration was determined from the residue after evaporating the contained water. (4) pH: Measured at 25°C using a D-51 instrument (manufactured by Horiba, Ltd.). (5) Viscosity: Measured at 25°C using a VM-10A instrument (manufactured by Sekonic Corporation). (6) Methanol concentration: Measured using GC-2025 (Shimadzu Corporation) as the instrument. (7) Denaturation rate (reaction rate of modification of anionic groups): Using a Dionex Integrion HPIC system (Thermo Fisher Scientific Co., Ltd.) as the instrument, each colloidal silica sample obtained in each example and comparative example was diluted 100 times with pure water (approximately 0.2% by mass solution), ultrafiltered, and 1 mL was taken and measured by anion chromatography. The measurement conditions were as follows.
[0101] (Measurement conditions) Eluent: Na2CO3 (1.8mM) + NaHCO3 (1.7mM), flow rate: 1.5mL / min, temperature: 35.0℃, injection volume: 1mL.
[0102] (Calculation of the degeneration rate) The denaturation rate was calculated using the following formula, where the amount of modification (mol) was determined by subtracting the amount of sulfate ions A (mol), which was quantified by anion chromatography, from the amount of 3-mercaptopropyltrimethoxysilane B (mol), which was added for the denaturation treatment of colloidal silica. Degeneration rate (%) = 100 × (BA) / B [Industrial applicability]
[0103] The colloidal silica of the present invention is suitable for applications such as abrasives (silicon wafers, hard disks, etc.), coatings (eyeglasses, displays, building materials, paper, etc.), and binders (ceramics, catalysts, etc.).
Claims
1. A method for producing colloidal silica whose surface is anionically modified, A raw material preparation step involves supplying and reacting readily hydrolyzable organosilicate with a reaction solution containing a hydrolysis catalyst made of an organic amine to prepare the raw material colloidal silica, A concentration adjustment step is performed to set the solid content concentration of the raw material colloidal silica to 13% by mass or less, and the concentration of alcohols generated from the raw material preparation step to 1 to 25% by mass, A modification treatment step for modifying the concentration-adjusted raw material colloidal silica, The process includes a concentration step of concentrating the modified colloidal silica so that the residual organic solvent in the modified colloidal silica is 1% by mass or less. A method for producing colloidal silica, characterized in that the modification rate of the modification treatment in the modification treatment step is 90% or more.
2. The method for producing colloidal silica according to claim 1, characterized in that the modification rate in the modification treatment step is 95% or more.
3. The method for producing colloidal silica according to claim 1 or 2, characterized in that the pH during the modification treatment in the modification treatment step is 8.0 or less.
4. The method for producing colloidal silica according to claim 1 or 2, characterized in that the raw material preparation step is carried out under conditions where the supply rate of the easily hydrolyzable organosilicate is less than 1.5% by mass of the total amount of the easily hydrolyzable organosilicate added per minute, the reaction time is within 6 hours, and the reaction temperature is 80°C or lower.
5. The method for producing colloidal silica according to claim 1 or 2, characterized in that the concentration step is performed to concentrate the colloidal silica after the modification treatment step so that the solid content concentration is 15% by mass or more.
6. The method for producing colloidal silica according to claim 1 or 2, characterized in that the raw material preparation step involves preparing raw material colloidal silica having a cumulant average diameter greater than 20 nm as measured by dynamic light scattering.
7. The method for producing colloidal silica according to claim 1 or 2, characterized in that the modification treatment step includes a step of reacting a modifying agent having a functional group that can be converted into an anionic group with the colloidal silica after the concentration adjustment step, and a step of converting the functional group in the modifying agent after the reaction into an anionic group.
8. The method for producing colloidal silica according to claim 7, characterized in that the modifying agent has a mercapto group and / or a sulfide group, and the mercapto group and / or sulfide group are converted to a sulfo group by treatment with an oxidizing agent to obtain colloidal silica having a sulfo group on its surface.
Citation Information
Patent Citations
Method for producing neutral colloidal silica
JP2007153732A
Modified colloidal silica, method of producing same, and polishing agent using same
WO2016117560A1
Colloidal silica and production method therefor
WO2025018234A1